Lifting the Veil of Words: An Analysis of the Efficacy of Chinese Takeover Laws and the Road to a Harmonious Society - Weng, Charlie Xiao-chuan (Columbia Journal of Asian Law, 2012)
Empirical evidence shows that takeovers are value-maximizing events for target firm shareholders and promote social efficiency. Takeovers are commonly thought to play a key role in reducing managerial slack in corporate governance through the replacement of inefficient management. Additionally, a multitude of economic literature indicates that synergy can result in the value of a combined firm that exceeds the sum of the values of two individual firms. But despite the potential for a value-creation event, takeovers rarely happen in China’s capital market. One reason for this phenomenon is that Chinese takeover laws have a chilling effect on potential corporate raiders. The pro-state-owned enterprise (SOE) approach of the China Securities Regulatory Commission (CSRC) further deters potential takeovers. This pro-government approach comes at the cost of non-SOE shareholders’ opportunities for value maximization. Nonetheless, since the Chinese government’s policy focus has shifted from protecting state-owned assets to promoting social equity, we can expect the CSRC’s regulatory approach to undergo significant changes as well. And in accordance with the change in the government’s core values, many takeover provisions need to be amended to facilitate value creation events at both state-owned and privately-owned firms.